2016
DOI: 10.1093/geronb/gbw010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Different Trajectories of Delay Discounting in Older Adults With Mild Cognitive Impairment and Mild Alzheimer’s Disease

Abstract: Our results point toward an increase in DD as a function of advanced cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…Our data have revealed that synapses of Aldh1a1 neurons are degenerated and associated with the impairments of the behavioral options for a large delayed reward. This finding supports the previous reports that impulsive behaviors occur in the early stage of human patients with AD [ 39 , 40 ]. Notably, an early study indicates that AD patients displayed significantly difference from control group in the degree of impulsive behaviors at one-month or one-year delay assay, but they had no difference from control group in the degree of impulsive behaviors at ten-years delay measurements [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data have revealed that synapses of Aldh1a1 neurons are degenerated and associated with the impairments of the behavioral options for a large delayed reward. This finding supports the previous reports that impulsive behaviors occur in the early stage of human patients with AD [ 39 , 40 ]. Notably, an early study indicates that AD patients displayed significantly difference from control group in the degree of impulsive behaviors at one-month or one-year delay assay, but they had no difference from control group in the degree of impulsive behaviors at ten-years delay measurements [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…Impulsive behavior occurs at the early stage of AD [ 39 , 40 ]. Subsequently, we examined Aldh1a1 → EGNIS synaptic transmission in heterozygous APPswe/PSEN1dE9 mutant mice (AD mice) carrying a transgene encoding the 695-amino-acid isoform of the human Aβ precursor protein with the Swedish mutation and a mutant human presenilin1 (PS1-dE9), which displayed impulsive behaviors when they were 5 months old, as compared with non-transgenic control C57BL/6 mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We set the upper age limit at 63 years to limit the potential confounding effect of older age. Older adults may show a greater preference for immediate over delayed rewards [35], and this preference may be stronger among older adults with mild cognitive impairment [36-38] and Alzheimer disease [37,38]. On the other hand, other studies indicate that older adults may show a greater preference for delayed rewards compared with middle-aged adults [36].…”
Section: Methodsmentioning
confidence: 99%
“…People with MCI may display significantly higher levels of DD, which indicates that they tend to respond to smaller rewards impulsively (Lindbergh et al, 2014). Compared to MCI patients and older adults, AD patients display even higher DD (Lebreton et al, 2013;Thoma et al, 2017;El Haj et al, 2020;Geng et al, 2020). These findings are probably related to impaired autobiographical memory in patients with AD (El Haj et al, 2020) and executive function deficits in patients with MCI (Geng et al, 2020).…”
Section: Cognitive Impairmentmentioning
confidence: 99%